Multi‐contingency TSCOPF based on full‐system simulation. Issue 1 (1st January 2017) - Ledesma, Pablo; Calle, Ignacio Antonio; Castronuovo, Edgardo Daniel; Arredondo, Francisco
Abstract : Transient stability constrained optimal power flow (TSCOPF) is a non‐linear optimisation problem used to perform economic dispatches while ensuring TS. This study proposes a multi‐contingency TSCOPF model that retains the dynamics of all generators and includes a transient synchronous generator fourth‐order dq ‐axis model. A program is developed that automatically reads the system data from standard files, builds the multiple‐contingency TSCOPF model on a high‐level modelling system and solves it using a non‐heuristic interior point algorithm. This approach facilitates the application of the model to a variety of systems and scenarios. A TSC based on the speed deviation instead of the rotor angle is proposed. Results obtained on several standard systems are shown. The proposed method is applied to the northwest Spanish transmission system to obtain an optimised dispatch that ensures TS after any of a number of faults, and to assess the economic impact of fault‐clearing times at different substations.